ASYMMETRIC CLOPEN SETS IN THE BITOPOLOGICAL SPACES - Dochviri, Irakli; Noiri, Takashi (Italian Journal of Pure and Applied Mathematics, 2014)
In the paper the behavior of clopen sets in bitopological spaces and some properties of generalized objects (e.g., (i, j)-quasi components and (i, j)-clopen compact subsets) are investigated. By using asymmetric clopen sets we introduce new classes of (i, j)-clopen irresolute and (i, j)-weakly clopen-continuous maps. Also, some their relations to p-ultra-Hausdorﬀ bitopological structures are established. Characterizations and a preserving theorem of pairwise connected spaces are obtained.